2005
DOI: 10.1111/j.1440-1797.2005.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin‐resistant anaemia in a predialysis patient with Klinefelter syndrome

Abstract: A diabetic predialysis patient who had significantly reduced sensitivity to erythropoietin therapy was admitted to Tsukuba University Hospital. Many factors that might have been the cause of the erythropoietin resistance were examined, and a diagnosis of refractory anaemia was made based on a bone marrow aspiration biopsy. A cytogenetic abnormality (47, XXY) was also detected in the bone marrow biopsy specimen, and hence the patient was also diagnosed with Klinefelter syndrome. It was suspected that the sex ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…These include stimulation of erythropoietin release, increasing bone marrow activity and iron incorporation into the red cells. Shimizu et al [4] have reported a Klinefelter syndrome patient with anemia due to erythropoietin resistance. Furthermore, deficiency of androgens can cause abnormal activation of T cell.…”
Section: Discussionmentioning
confidence: 99%
“…These include stimulation of erythropoietin release, increasing bone marrow activity and iron incorporation into the red cells. Shimizu et al [4] have reported a Klinefelter syndrome patient with anemia due to erythropoietin resistance. Furthermore, deficiency of androgens can cause abnormal activation of T cell.…”
Section: Discussionmentioning
confidence: 99%